Precision attachments for partial edentulous rehabilitation - Nur Inriany; Herawati Hasan; Irfan Dammar (Indonesia Prosthodontic Association, 2023)
A 48-year-old female patient was referred to the Department of Prosthodontic, Hasanuddin University Dental Hospi-tal, Makassar with complaints of difficulty chewing food due to partial tooth loss. The patient had used a denture on the lower jaw but it was loose so she wanted to make a denture on both jaws without using wires so as not to disturb the aesthetics. Intra-oral examination, the upper jaw was left with nine teeth with gingival recession and the lower jaw was totally edentulous. A hybrid denture that could support the patient's aesthetics and a conventional complete denture in the lower jaw were fabricated. Initially, a preliminary mold and study model were made, then temporary vertical dimensions were determined followed by recording the relationship of the maxilla and mandible using the two dots method, and mounted on an articulator. Preprosthetic treatment included scaling, endodontic treatment. Preparation of teeth 13, 14, 24, and 25 for porcelain-fused to metal. It is concluded that precision attachment in den-tistry is the functional mechanical part of a removable partial denture. The use of precision-attached dentures has simplified and strengthened the retention, function and aesthetic aspects when compared to conventional remova-ble partial dentures.